Molecular tension in syndecan-1 is regulated by extracellular mechanical cues and fluidic shear stress. (August 2021) - Le, Victoria; Mei, Lei; Voyvodic, Peter L.; Zhao, Chi; Busch, David J.; Stachowiak, Jeanne C.; Baker, Aaron B.
Abstract: The endothelium plays a central role in regulating vascular homeostasis and is key in determining the response to materials implanted in the vascular system. Endothelial cells are uniquely sensitive to biophysical cues from applied forces and their local cellular microenvironment. The glycocalyx is a layer of proteoglycans, glycoproteins and glycosaminoglycans that lines the luminal surface of the vascular endothelium, interacting directly with the components of the blood and the forces of blood flow. In this work, we examined the changes in mechanical tension of syndecan-1, a cell surface proteoglycan that is an integral part of the glycocalyx, in response to substrate stiffness and fluidic shear stress. Our studies demonstrate that syndecan-1 has higher mechanical tension in regions of cell adhesion, on and in response to nanotopographical cues. In addition, we found that substrate stiffness also regulated the mechanical tension of syndecan-1 and altered its binding to actin, myosin iiB and signaling intermediates including Src, PKA and FAK. Application of fluidic shear stress created a gradient in tension in syndecan-1 and led to enhanced association with actin, Src, myosin IIb and other cytoskeleton related molecules. Overall, our studies support that syndecan-1 is responsive to the mechanical environment of the cells and alters its association with actin and signaling intermediates in response to mechanical stimuli.